EL Vínculo universidad y derechos humanos (Società e diritti, 2021)
AbstractStates have increasingly expressed the consensus that human rights education contributes decisively to the realization of human rights. Human rights education aims to foster an understanding that each individual shares responsibility for making human rights a reality in each community and in society as a whole. In this sense, it contributes to the long-term prevention of human rights abuses and violent conflict, the promotion of equality and sustainable development, and the enhancement of people's participation in decision-making processes within democratic systems. It is now even asserted that human rights education is not only intended to respond to the demands of civil society for political participation in the policies that concern it and in situations such as the development of technology, the environment, community or other conflicts, manifestations of intolerance, etc., but also to articulate an educational approach that favours democracy, development and peace.